LOYALITAS PELANGGAN PADA BISNIS RETAIL DARI SUDUT PANDANG RELATIONSHIP MARKETING - Kusumawati, Andriani (FIA UB, 2007)
Retailer require to â€œcreateâ€ loyal and finatical buyer and also which comprehend the important of product quality without too confused by price tough a little higher than is other. He also have to can create â€œshopping cultureâ€ to consumer, so that can draw customer as much as possible passing effort of relationship marketing. Marketer expected can run correct tactics to play in every step enchain behavior of the expense so that consumer can satisfy and finally loyal to shop. Strive shop loyalty also require to be conducted because will affect shop business performance. This researchaim to depict Customer Loyalty in Retail Business From The Relationship Marketing Perspective and explain influence of Relationship Marketing to Customer Loyalty in Retail Business with Customer Satisfaction as intervening variable. The result of this of research expressed that in general applying of Relationship Marketing in Hypermart Malang Town Square have goodness. Conception the conducted sale in place by applying discount at certain days as effort pamper individual consumer which shop at there. Besides, going into effect also reward poin use Matahari Club Card (MCC) as exist in Matahari Department Store. Other program which do not fail drawing it is the existance of program check lotery and price which is very captivate customer to continue to go shopping. This kind of model it is true represent new metter to consumer in Malang City, so that do not surprise if more opting consumer of this place as family expense medium as well as recreation area with. Changing over of it consumer to shopping centre which is one this is not quit of applied effort to its consumer to give promise in the form of guarantee will the quality of product, price, promotion program and better service